IDENTIFYING AND ANALYZING CHALLENGES IN ADMINISTERING CONSTRUCTION CONTRACTS OF THE LARGE PUBLIC PROJECTS IN BHUTAN - Gyem, Tandin; Likhitruangsilp, Veerasak (การประชุมวิศวกรรมโยธาแห่งชาติครั้งที่ 26, 2021)
Construction projects encompass three major phases: the design phase, the construction phase, and the operation phase. Although problems are inevitable in every project phase, most of them are encountered during the construction phase. A construction contract is a formal agreement between the contracting parties. An important contract document is the conditions of contract, which entails the rules and regulations to administer the contract. In Bhutan, all public construction projects are mandated to follow the Bhutan Procurement Rules and Regulations 2019 and the Standard Bidding Documents for procurement of works 2019. Although these documents are updated regularly, the contract administration is often faced with various challenges. This paper identifies major gaps between the existing construction contract and the contract administration of the public projects in Bhutan. To identify the challenges in the contract administration, we conduct in-depth interviews with a group of local procurement professionals, government engineers, and contractors. As per the interviews, 18 out of 26 challenges in the large public projects in Bhutan have been faced during the construction phase. The survey questionnaires are then prepared based on these 18 challenges to measure the likelihood of occurrence and their impacts in terms of time, cost, and quality of the project. Subsequently, these 18 challenges are classified into three groups using an likelihood of occurrence-impact matrix. The identified challenges in administering the construction contracts of the large public projects in Bhutan can help the government authorities make rational decisions and enhance the efficiency of the existing standard form of construction contract in Bhutan. Keywords: (Bhutan Construction Industry, Construction Contract, Large Public Projects, General Conditions of Contract, Standard Bidding Document)